Kemampuan Menghafal Al-Quran Ditinjau dari Kecerdasan Matematis Santriwati - Risnamajasari, Risnamajasari; Sakiya, Nur (Program Studi Pendidikan Matematika, 2024)
The research aims to determine the ability to memoriza the Al-Quran in terms of mathematical intelligence. The type of research used is qualitative research with a desciptive approach. Data was collected through observation and interviews, with a total of six research subjects. The research result show that: 1. Student with high mathematical intelligence tend to have the ability to memorize the Al-Quran well, the amount of memorization is large, and the time required to memorize the Al-Quran is fast. 2. Student with moderate mathematical intelligence tend to have moderate ability to memorize the Al-Quran, a moderate amount of memorization and require a moderate amount of time, 3. Student with low mathematical intelligence tend to have poor ability to memorize the Al-Quran, the amount memorization is small, and the spend more time memorizing the Al-Quran. 4. Student who have the ability to memorize the Al-Quran well tend to have the ability to memorize the Al-Quran well too.